2019
DOI: 10.1186/s40657-019-0142-0
|View full text |Cite
|
Sign up to set email alerts
|

Mercury concentrations in blood and feathers of nestling Bald Eagles in coastal and inland Virginia

Abstract: Background: Mercury (Hg) and methylmercury are widely considered significant issues for wildlife, and in particular, piscivorous birds due to their widespread availability and neurotoxic properties. Whereas a substantial number of studies of Hg contamination of Bald Eagles (Haliaeetus leucocephalus) have been conducted throughout the east coast of the United States, little has been done that directly addresses Hg contamination in Bald Eagles in Virginia, particularly the inland population. Methods: We collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…These species could be used as bioindicators to evaluate the plastic pollution burden in different environments because they have been well studied in the past two decades. In addition, as long-lifespan species (e.g., albatrosses, shearwaters, and vultures) can breed over many decades (Moore 2008 ), they could be used to evaluate the potential toxicological effects of chronic plastic exposure on both individual survival and reproductive output (Kramar et al 2019 ; Marín-Gómez et al 2020 ; Sánchez et al 2020 ). Furthermore, these species could be used to evaluate the effects of food contaminated with plastic debris and the intergenerational transfer of MPs through allofeeding of offsprings (Sánchez et al 2020 ), as observed in the Cory’s Shearwater ( Calonectris diomedea ) fledglings (Rodríguez et al 2012 ), Providence Petrel ( Pterodroma solandri ) (Bester et al 2010 ), Black-footed Albatross ( Phoebastria nigripes ) (Rapp et al 2017 ), Laysan Albatross ( P. immutabilis ) (Young et al 2009 ), Short-tailed Shearwater (Carey 2011 ), Wedge-tailed Shearwater ( A. pacifica ) (Verlis et al 2013 ), Flesh-footed Shearwater (Lavers et al 2014 ), and other petrels (Rapp et al 2017 ).…”
Section: Future Directionsmentioning
confidence: 99%
“…These species could be used as bioindicators to evaluate the plastic pollution burden in different environments because they have been well studied in the past two decades. In addition, as long-lifespan species (e.g., albatrosses, shearwaters, and vultures) can breed over many decades (Moore 2008 ), they could be used to evaluate the potential toxicological effects of chronic plastic exposure on both individual survival and reproductive output (Kramar et al 2019 ; Marín-Gómez et al 2020 ; Sánchez et al 2020 ). Furthermore, these species could be used to evaluate the effects of food contaminated with plastic debris and the intergenerational transfer of MPs through allofeeding of offsprings (Sánchez et al 2020 ), as observed in the Cory’s Shearwater ( Calonectris diomedea ) fledglings (Rodríguez et al 2012 ), Providence Petrel ( Pterodroma solandri ) (Bester et al 2010 ), Black-footed Albatross ( Phoebastria nigripes ) (Rapp et al 2017 ), Laysan Albatross ( P. immutabilis ) (Young et al 2009 ), Short-tailed Shearwater (Carey 2011 ), Wedge-tailed Shearwater ( A. pacifica ) (Verlis et al 2013 ), Flesh-footed Shearwater (Lavers et al 2014 ), and other petrels (Rapp et al 2017 ).…”
Section: Future Directionsmentioning
confidence: 99%
“…This procedure is the best method used in most bird species, because many species do not have other blood vessels large enough for venipuncture (Stevens and Ridgway 1966). In recent studies, the methods of blood collection are not very detailed (Kramar et al 2019) even if this is a common procedures. In the following details, all the steps are listed to ensure optimal reproducibility of the work.…”
Section: Hematological Parametersmentioning
confidence: 99%